Understanding variations in the use of tranexamic acid in surgery: a qualitative interview study - Strickland, L; Evans, H; Palmer, A; Warnakulasuriya, S; Murphy, M; Stanworth, S; Foy, R (Wiley, 2025)
Despite robust supporting evidence, around a third of eligible surgical patients do not receive tranexamic acid (TXA). Effective strategies based on an understanding of clinical behaviour are needed to increase use and improve patient outcomes. We conducted semi-structured interviews with clinicians involved in perioperative care to explore perceived influences on TXA use. We identified key influences on practice using the theoretical domains framework. We matched these to behaviour change techniques and evidence-informed implementation intervention components. Across 22 interviews, we identified eight key influences within three overarching themes of capability, opportunity and motivation. Capability influences included the clinical context and variable familiarity with TXA. Opportunity concerned the availability of both TXA and checklists to support decision-making and whether TXA use was consistent with professional expectations and perceived responsibilities. Motivation concerned confidence in administering TXA, perceived benefits and risks and training received around potential risk factors. These influences varied across participants and specialities. Our resulting proposed implementation strategy included training, clinical prompts, comparative performance feedback and opinion leadership supported by specialty-specific guidance. Any strategy to increase TXA use that improves knowledge and skills without addressing wider influences on clinical behaviour is only likely to meet with limited success.